The Role of High Spatial Frequencies in Face Perception. (November 2013) - Fiorentini, Adriana; Maffei, Lamberto; Sandini, Giulio
The relevance of low and high spatial-frequency information for the recognition of photographs of faces has been investigated by testing recognition of faces that have been either low-pass (LP) or high-pass (HP) filtered in the spatial-frequency domain. The highest resolvable spatial frequency was set at 15 cycles per face width (cycles fw −1 ). Recognition was much less accurate for images that contained only the low spatial frequencies (up to 5 cycles fw −1 ) than for images that contained only spatial frequencies higher than 5 cycles fw −1 . For faces HP filtered above 8 cycles fw −1, recognition was almost as accurate as for faces LP filtered below 8 cycles fw −1, although the energy content of the latter greatly exceeded that of the former. These findings show that information conveyed by the higher spatial frequencies is not redundant. Rather, it is sufficient by itself to ensure recognition.